THE EFFECTIVENESS OF STORYTELLING METHOD THROUGH RITATOON ON THE ABILITY TO LISTEN TO AGE CHILDREN 5-6 YEARS TK IT PERMATA SUNNAH BANDA ACEH - Riza Oktariana; Mita Rezekina; Wahidah Nasution; Liza Fidiawati; Fitriani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Storytelling is an event that is carried out by someone verbally to another person with or without tools about what to convey in the form of messages, information to be listened to with a sense of fun. While the storytelling method is a way of speaking in telling stories or giving explanations to children orally. The purpose of this study was to determine the effectiveness of the storytelling method through ritatoon in developing listening skills for children aged 5-6 years in Group B TK IT Permata Sunnah Banda Aceh. The method used is the experimental method then the data is analyzed quantitatively. The research sample for group B1 Khalid Bin Walid children is 12 children. The instruments used in this data collection were observation sheets and documentation. Based on the data analysis that has been done, the value (sig. 2-tailed) for the paired sample t-test for testing the hypothesis is 0.00. The test carried out is the right[1]hand side test, because 0.00